Exemplary compliance programmes in Brazilian firms in the wake of Brazil's anti-corruption movement - Bannister, Sophie (2019)
The involvement of companies in corrupt acts is one of the main threats to continued social support for private businesses. This study’s literature centred on organisational-level corruption in Brazil – considered one of the most corrupt countries in the world - and its possible solution in the form of compliance programmes that detect and prevent corporate violations of law. The revised literature showed that, since 2013, the number of companies in Brazil with compliance programmes in place has increased significantly, mainly as a response to the growing implementation of anti-corruption legislation in Brazil, such as the enactment of the Clean Company Act (“CCA”) law in 2013 and the fear of implication in major Brazilian ongoing corruption investigations which have already tarnished the reputations of many corrupt companies. This study’s literature review also showed, however, that despite Brazil’s growing adherence to corporate compliance programmes, a significant portion of companies in Brazil still have poor compliance policies in place. In order to address this problem, this study looked at the specific compliance processes implemented by a select group of companies in Brazil considered to have reputable compliance programmes in place. As well as assessing what sets these companies apart from most other companies in the country, this study looked at what motivated them to implement or reinforce their compliance programmes, as well as which benefits they reaped or difficulties they faced in the process, as a means of providing practical knowledge for other companies in Brazil that wish to join the country’s current anti-corruption movement. This was done by analysing the reputable compliance programmes of 11 Brazil- based companies. Primary data was drawn from in-depth qualitative interviews with six companies, while publicly available secondary data in the form of interviews given by five other companies was also collected and analysed. The results of this analysis indicated that efficient compliance programmes in Brazil must be constituted of leadership, risk assessment, standards and controls, training and communication, oversight, and constant improvement practices. The fact that several companies were found to have been “pushed” into implementing or reinforcing compliance programmes, allied to the fact that, as well as numerous reaped benefits, they also faced certain cultural and operational difficulties in the process, corroborated previous research and testified to the importance of further studies being conducted into this same topic.